Effects of Chronic and Acute Zinc Supplementation on Myocardial Ischemia-Reperfusion Injury in Rats - Ozyildirim, Serhan; Baltaci, Abdulkerim Kasim; Sahna, Engin; Mogulkoc, Rasim (Humana Press Inc, 2017)
The present study aims to explore the effects of chronic and acute zinc sulfate supplementation on myocardial ischemia-reperfusion injury in rats. The study registered 50 adult male rats which were divided into five groups in equal numbers as follows: group 1, normal control; group 2, sham; group 3, myocardial ischemia reperfusion (My/IR): the group which was fed on a normal diet and in which myocardial I/R was induced; group 4, myocardial ischemia reperfusion + chronic zinc: (5 mg/kg i.p. zinc sulfate for 15 days); and group 5, myocardial ischemia reperfusion + acute zinc: the group which was administered 15 mg/kg i.p. zinc sulfate an hour before the operation and in which myocardial I/R was induced. The collected blood and cardiac tissue samples were analyzed using spectrophotometric method to determine levels of MDA, as an indicator of tissue injury, and GSH, as an indicator of antioxidant activity. The highest plasma and heart tissue MDA levels were measured in group 3 (p < 0.05). Group 5 had lower MDA values than group 3, while group 4 had significantly lower MDA values than groups 3 and 5 (p < 0.05). The highest erythrocyte GSH values were found in group 4 (p < 0.05). Erythrocyte GSH values in group 5 were higher than those in group 3 (p < 0.05). The highest GSH values in heart tissue were measured in group 4 (p < 0.05). The results of the study reveal that the antioxidant activity inhibited by elevated oxidative stress in heart ischemia reperfusion in rats is restored partially by acute zinc administration and markedly by chronic zinc supplementation.
Keywords: Myocardial ischemia reperfusion; Acute and chronic zinc supplementation; Antioxidant activity